Productive Performance of Laying Japanese Quail Fed Diets Containing Babadotan (Ageratum conyzoides) Leaf Meal - Deden Sudrajat; Annisa Qurrotu Aini; Anggraeni (Universitas Djuanda, 2026)
This study evaluated the effect of babadotan (Ageratum conyzoides) leaf meal supplementation on the egg productivity of Japanese quail (Coturnix coturnix japonica). A completely randomized design was applied using four dietary treatments: 0% (R0), 1% (R1), 3% (R2), and 5% (R3) babadotan leaf meal. A total of 140 female quails aged 6–12 weeks were observed for six weeks. The parameters measured were egg weight, quail day production, egg mass, feed conversion ratio (FCR), and mortality. The nutrient composition of the diets was relatively similar among treatments, with crude protein ranging from 22.48% to 22.61%, while crude fiber increased slightly as the inclusion level of babadotan leaf meal increased . The results showed that babadotan leaf meal supplementation had no statistically significant effect on egg productivity. Egg weight increased slightly from 10.39±0.29 g in R0 to 10.53±0.13 g in R3, but the difference was not significant. Quail day production was highest in the control group (44.56±3.54%) and lowest in R2 (36.06±10.55%), while FCR was most efficient in the control group (5.09±0.74) and tended to worsen in the supplemented groups . Mortality remained 0% across all treatments, indicating that all birds were maintained in good health during the experiment. In conclusion, supplementation of babadotan leaf meal up to 5% did not significantly improve the egg productivity of Japanese quail, although it could be included without negative effects on bird health .